Economic Synergy between Dry Cow Diet Improvement and Monensin Bolus Use to Prevent Subclinical Ketosis: An Experimental Demonstration Based on Available Literature - Raboisson, Didier; Barbier, Maxime (Frontiers in Veterinary Science, 2017)
The prevention of subclinical ketosis (SCK) is based on maintaining adequate nutrition in dairy cows during the dry period and close to calving. Recently, an oral-route monensin bolus to prevent SCK was approved in Europe. The present study aims to define the allocation of resources for SCK management at the herd level and evaluate the profitability of administering monensin boluses in cows at risk for SCK. A stochastic model was used to calculate the total cost of SCK for a population with a given prevalence of cows at risk for SCK. This model included the ability of the farmer to correctly target and preventatively treat these cows at risk for SCK. The results clearly demonstrated economic synergy between two management practices. First, reducing the prevalence of cows at risk for SCK dramatically reduces the total cost of SCK and seems profitable in most situations. Second, monensin bolus use to reduce the occurrence of SCK in cows already at risk for SCK is cost-effective. The results also highlighted 3 economic strategies to manage SCK in the dairy industry in Europe. First, monensin bolus use throughout an entire herd when the prevalence of cows at risk for SCK is high is only profitable in the short-term as a tool to correct acute deterioration at the herd level. Second, decreasing the prevalence of cows at risk for SCK through adequate feeding in the dry period is of financial interest as a baseline strategy when prevalence is high, assuming moderate additional cost linked to the new diet. Third, monensin bolus use when the prevalence of cows at risk for SCK is low is also profitable as a long-term strategy when only cows at high risk for SCK (such as cows that are over-conditioned, old, or have a previous history of SCK-related disorders) are targeted for preventative treatment. Authors suggest to use the present results considering that farmers have a correct, but not perfect, ability to target animals to be preventively targeted with the monensin bolus. Further work is required to facilitate the early identification of cows at risk for SCK.